Preparing Kindergarden Teachers for the Complex Field of Education - Šagud, Mirjana (2008)
Preparing kindergarden teachers for the new conditions within an institutional context should be viewed in the light of systematic and continuing changes that take place, along with their greater professional responsibility and autonomy in making practical decisions. The new paradigm for teacher education, increasingly includes, in the group of the necessary components of professional competence, the development of skills for the research of the immediate educational situation with the aim of verifying different strategies or approaches within this particular context. Different approaches exist in education research, as well as different roles and positions of teachers. Teachers as objects are predominantly isolated from scientific research, since this activity is mainly initiated and conducted from the outside. Therefore the results are often irrelevant to the teaching process or their practical implications are not recognizable (decontextualized results). Since learning and education are complex processes, no theory or research results can be derived from this activity ; nor actual individual educational experience can give ready answers or guidance for solving problems in an actual educational context ; nor can research results be seen as standardized or universal. Therefore, a traditionally educated teacher needs to develop into a reflexive professional who continuously builds his/her ability for theoretical reflections in practice and vice versa, and through practice and contemplation, builds a new theory. Educating a reflective practitioner is a new conceptual as well as methodological approach to teaching usually based on action research that appears in opposition to technical and rational (traditional) model of teacher education. Kindergarten teachers who participate in action research actually participate in the intensive program of lifelong learning and through reflection of educational process actually develop personal and professional competence necessary for productive teaching. Participation in action research, the ability for continuous professional learning and progress through the reflection of one’s own work and estimate of its efficiency in cooperation with colleagues are some of the ways in which “a new teacher” can undertake more responsibility for their own teaching.
Projekt MZOS
ENG